High-Strength and Stretchable Fabric-Reinforced Hydrogel Composites: Their Applications on the Removal of Methylene Blue - Koc, Umit; Aykut, Yakup; Eren, Recep (Korean Fiber Soc, 2025)
The present paper reports a research for the preparation of the highly stretchable fabric-reinforced composite with enhanced mechanical properties. Removal of methylene blue (MB) from aqueous solution was studied using Cotton-polyvinyl alcohol (PVA) fibers woven fabric reinforced hydrogel composite with enhanced mechanical stability. The composite hydrogel comprised tetraethyl orthosilicate (TEOS) as the crosslinking agent. The morphology and properties of PVA/Cotton fabric reinforced hydrogel composites were characterized through Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimeter (DSC), thermogravimetric analyzer (TGA), X-ray diffraction (XRD) and scanning electron microscopy (SEM). Moreover, the electrochemical measurements of the MB were investigated using the differential pulse voltammetry (DPV) method, and the interaction between MB and TEOS-treated PVA/Cotton fabric was investigated using ultraviolet-visible (UV-vis) spectroscopy. Through this study, compared with the neat PVA/Cotton fabric breaking force in warp direction (664.74 N), increasing the TEOS ratio from 3% vol. to 100% vol. caused breaking force to increase properly to 22.37, 29.29, 64.04 and 72.27 N, respectively. The breaking force in weft direction decreased from 181.03 N (3% vol. TEOS concentration) to 138.77 N (10% vol. TEOS concentration) while it gradually increased from 225.65 (30% vol.) to 236.88 N (100% vol.). It can be concluded that PVA/Cotton fabric reinforced hydrogel composites with improved mechanical stability could be used as a potential adsorbent material to remove the MB dye from an aqueous solution.
Keywords: Stretchable hydrogel; Methylene blue removal; Polyvinyl alcohol; Tetraethyl orthosilicate; Woven fabric; Adsorption efficiency; Mechanical improvements